Establish Federal Agricultural Extension Service in D.C : hearings before the United States House Committee on Agriculture, Subcommittee on Research and Extension, Ninetieth Congress, first session, on Oct. 9, 1967. (U.S. Congressional Hearings., 1967)
Committee Serial CC. Considers H.R. 10756 and similar bills, to authorize USDA to establish and maintain a Cooperative Extension Service in the District of Columbia.